Late‐onset allograft rejection, cytomegalovirus infection, and renal allograft loss: Is anti‐CMV prophylaxis required following late‐onset allograft rejection?. Issue 6 (23rd March 2021) - Rahimishahmirzadi, Mohammadreza; Jevnikar, Anthony M.; House, Andrew A.; Luke, Patrick P.; Humar, Atul; Silverman, Michael S.; Shalhoub, Sarah M.; Hosseini‐Moghaddam, Seyed M.
Abstract: Renal transplant recipients remain at risk of delayed‐onset cytomegalovirus (CMV) infection occurring beyond a complete course of prophylaxis. In this retrospective cohort, all 278 patients who received renal allografts from deceased donors from 2014 to 2016 were followed until September 1, 2019. We determined the effect of early–vs late‐onset acute rejection (EAR vs LAR [ie, occurring beyond 12 months after transplantation]) on CMV infection and subsequently long‐term allograft outcome. Median (IQR) duration of follow‐up was 1186.0 (904.7‐1531.2) days. Seventy patients including 49 patients with EAR and 21 with LAR received augmented immunosuppression. In the same interval, 40 patients developed CMV infection (36 patients beyond 90 days after transplantation [90%]). In logistic regression analysis, D+/R‐ CMV serostatus (OR: 5.5, 95% CI: 2.5‐12.2) and LAR (OR: 7.9, 95% CI: 2.8‐22.2) significantly increased the risk of CMV infection. In Cox proportional hazard model, delayed‐onset CMV infection (HR: 2.51, 95% CI: 1.08‐5.86) and LAR (HR: 5.46, 95% CI: 2.26‐13.14) significantly increased the risk of allograft loss. Patients with LAR are at risk of late‐onset CMV infection. Post‐LAR, targeted prophylaxis may reduce the risk of CMV infection and subsequently allograft loss. Further studies are required to demonstrate the effect of targeted prophylaxis following LAR.